Advances in mergers and acquisitions. Vol. 6 - Finkelstein, Sydney; Cooper, Cary L. (Emerald, 2007)
Mergers and acquisitions continue to be a primary vehicle of growth for companies around the world. Not only in the United States and Europe, but also in Japan, China, India, Brazil and elsewhere senior executives are making huge bets on the future of their firms. With such intense scrutiny in the world of business, it is not surprising that academic research on mergers and acquisitions has been similarly robust. The topics range from strategy, to organizational integration, culture, leadership, human resource planning, and financial analysis.-Similarly, the theories brought to bear to help understand mergers and acquisitions range from upper echelons theory to the resource based view of the firm, competitive analysis, organizational trust, networks, knowledge management, and others.What makes the Advances in Mergers and Acquisitions series stand out is its focus on all three characteristics that make up this research field - studies from scholars in different countries, with different research questions, and relying on different theoretical perspectives. Such a broad, and inclusive, approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The collections published each year provide cutting edge ideas by leading scholars on a global scale. Doing so not only broadens the questions being studied, but also helps researchers consider the inter-relationships among different perspectives.-In the final analysis, the best way to build understanding around a topic as diffuse as mergers and acquisitions is to be both integrative, and expansive, in choice of research questions and theoretical underpinnings.Advances in Mergers and Acquisitions offers this unique perspective, not easily found elsewhere, that will help scholars think about mergers and acquisitions in new ways, building our knowledge base on this critical topic. In light of the enormous sums being invested in growth-via-acquisition strategies around the world, academic research on mergers and acquisitions has never been more important.
Keywords: Consolidation and merger of corporations.; Consolidation and merger of corporations -- Management.; elektronické knihy; electronic books